Social Studies Learning Management Model Based on Strengthening Character Education at SMP Negeri 2 Beduai, West Kalimantan - Endy Liani Klarita; Kosasih; Yuyun Yuniarsih; Farida Yuliaty (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to develop a learning management model of Social Studies (IPS) based on character education reinforcement at SMP Negeri 2 Beduai, West Kalimantan. The background of this research is the importance of integrating character values into the learning process to shape students who are not only intellectually competent but also morally responsible, disciplined, and caring individuals. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and then analyzed descriptively using the stages of data reduction, data display, and conclusion drawing. The findings reveal that the learning management of Social Studies based on character education reinforcement at SMP Negeri 2 Beduai is implemented through three main stages: (1) learning planning that integrates character values such as religiosity, honesty, social care, and responsibility; (2) learning implementation using collaborative strategies, discussions, and contextual problem-solving aligned with the local socio-cultural environment; and (3) learning evaluation emphasizing authentic assessment that includes cognitive, skill, and affective aspects. This model has been proven to increase students’ active participation, strengthen their sense of responsibility, and foster awareness of environmental sustainability and harmonious living in a multicultural society. Therefore, the Social Studies learning management model based on character education reinforcement can serve as a reference for teachers in creating a holistic, contextual, and relevant learning process in the era of globalization.